1972
DOI: 10.1080/00022470.1972.10469608
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenates in Exhaust from Simple Hydrocarbon Fuels

Abstract: Photochemical air pollution is known to be caused largely by automotive emissions such as hydrocarbons and oxygenated hydrocarbon derivatives. Unlike the hydrocarbons, the contribution of the oxygenates has been virtually unexplored, mainly because of lack of appropriate analytical methods. The objective of this study was to identify and estimate the levels of oxygenated hydrocarbon derivatives in exhaust from simple hydrocarbon fuels. This information is expected to yield ultimately estimates of the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…The general population is potentially exposed to 2,3-benzofuran (BF 4 ) through its release into the environment as a result of waste incineration (Junk and Ford, 1980) and from exhaust gases from gasoline and diesel engines (Seizinger and Dimitriades, 1972;Hampton et al, 1982). The use of BF in the manufacture of coumaroneindene resins is an industrial hazard and may result in environmental contamination with BF via various waste streams (Budavari, 1989).…”
mentioning
confidence: 99%
“…The general population is potentially exposed to 2,3-benzofuran (BF 4 ) through its release into the environment as a result of waste incineration (Junk and Ford, 1980) and from exhaust gases from gasoline and diesel engines (Seizinger and Dimitriades, 1972;Hampton et al, 1982). The use of BF in the manufacture of coumaroneindene resins is an industrial hazard and may result in environmental contamination with BF via various waste streams (Budavari, 1989).…”
mentioning
confidence: 99%
“…The result indicated the presence of nitro-organic compounds, such as nitromethane, nitrophenols, and dihydroxynitrobenzenes in diesel exhaust, along with hydrocarbons, aromatics, and oxygenated VOCs. The presence of acetonitrile in diesel-powered engine exhaust has been shown by means of PTR-MS [13,14], and vehicular exhaust has been shown to emit nitromethane [55] and gaseous nitrophenols by means of GC/MS [49,56].…”
Section: Nitro-organic Compounds In Vehicular Exhaustmentioning
confidence: 99%
“…Methyl isopropenyl ketone (MIK, H 2 C]C(CH 3 )C(O)CH 3 ) is an important a,b-unsaturated ketone and has been observed from anthropogenic sources (plants, solvent use, biomass burning, fossil fuel combustion, etc.). [1][2][3][4] In addition, MIK has been found to be an intermediate product in synthesis and in the catalysis industry. 5 It is reported that MIK can be widely used in the polymer manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although the reaction of MIK with OH radicals is generally considered to be the predominant degradation pathway among these various species, the reaction of MIK with Cl atoms also represents a signicant loss process in some special regions, such as coastal regions, the marine boundary layer and some polluted mid-continental regions with high chlorine emissions. [11][12][13] According to Chang's report, the average concentration of Cl atoms is estimated to be as high as 3 Â 10 5 molecules per cm 3 or more in the marine boundary layer. 14 In addition, the Cl atoms reactions with organic compounds have been reported to be much faster than OHparticipated reactions.…”
Section: Introductionmentioning
confidence: 99%